Formulation Strategies For Solubility Enhancement Of Fusidic Acid Using Solid Dispersion Techniques - B Survase, Abhijeet; A Khedkar, Samrat; H Nagane, Somnath (Journal of Neonatal Surgery, 2025)
Fusidic acid is a poorly water-soluble antibiotic that exhibits limited oral bioavailability due to its low dissolution rate. The present study aimed to enhance the solubility of fusidic acid using the solid dispersion technique. Solid dispersions were prepared by the solvent evaporation method employing hydrophilic carriers, namely polyvinylpyrrolidone (PVP K30) and polyethylene glycol (PEG 4000), at different drug-to-polymer ratios. The prepared formulations were evaluated for percentage yield, drug content, and physicochemical characteristics using Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis. The results demonstrated a significant improvement in the solubility and dispersion of fusidic acid in the presence of hydrophilic carriers. Among the formulations, those containing PVP K30 showed superior performance in enhancing drug release compared to PEG 4000, indicating its effectiveness as a carrier. FTIR studies confirmed the absence of significant drug–excipient interactions, while XRD analysis revealed a reduction in crystallinity, suggesting partial conversion of the drug into an amorphous form. The solid dispersion technique using PVP K30 is a promising approach for improving the solubility of fusidic acid. Further studies are recommended to evaluate long-term stability and in vivo performance.